CRT-BASED GO JAR APPLICATION FOR TEACHER PROFESSIONAL DEVELOPMENT AND ART LEARNING ACHIEVEMENT - Undiarsih, Indit; Hartinah, Sitti; Habibi, Beni (Al-Mubin, 2025)
This research is motivated by the increasing cultural crisis in the field of education, particularly in dance learning at SMP Negeri 3 Randudongkal. Many students struggle to recognize and appreciate local culture due to the use of general teaching materials that do not adequately consider their cultural context. This study aims to develop a learning application based on Culturally Responsive Teaching (CRT) that integrates local dance into the teaching and learning process. The Go Jar application features seven main menus: lesson planning instruments, teacher and student guidebooks, learning materials, student assessments, work evidence, videos, and worksheets (LKPD). This research employs the Research and Development (R&D) method, following Sugiyono's development model, which includes identifying potential and problems, data collection, product design, validation, testing, and product revision. Data collection techniques involve observation, interviews, document studies, and limited trials. The study involves students and cultural arts teachers as test subjects, as well as material and media experts for validation. The research results indicate that the development of the Android-based Go Jar learning application was successful and suitable for use as an interactive learning medium. The material expert validation achieved a score of 100%, indicating very high feasibility, while media expert validation received a score of 94%, categorized as feasible. The small group trial resulted in a score of 91.6%, classified as good, whereas the large group trial obtained a score of 92.1%, categorized as highly feasible. The Go Jar application serves as an innovation in cultural arts learning technology, facilitating students in understanding the local cultural identity of Pemalang and supporting teachers in developing more inclusive and interactive teaching methods.